Role of reactive oxygen species in lesion mimic formation and conferred basal resistance to Fusarium graminearum in barley lesion mimic mutant 5386 - Wang, Wenqiang; Zhang, Jifa; Guo, Fenxia; Di, Yindi; Wang, Yuhui; Li, Wankun; Sun, Yali; Wang, Yuhai; Ni, Fei; Fu, Daolin; Wang, Wei; Hao, Qunqun (Frontiers in Plant Science, 2022)
This study investigated barley lesion mimic mutant (LMM) 5386, it exhibited a leaf brown spot phenotype, localized on the chromosome 3H, and conferred basal resistance to F. graminearum. RNA-seq analysis identified 1453 differentially expressed genes in LMM 5368 compared to those in the wild type. GO and KEGG functional annotations suggested that lesion mimic formation was mediated by pathways involving oxidation-reduction and glutathione metabolism. In addition, the accumulation of reactive oxygen species (ROS) in brown spots was substantially higher in LMM 5368. Antioxidant competence, as indicated by ROS accumulation, was significantly lower in LMM 5368. Further, the reduction of glycine in LMM 5386 inhibited glutathione biosynthesis. These results suggest that the decrease in antioxidant competence and glutathione caused the accumulation of large amounts of ROS and thus led to programmed cell death in leaves of LMM 5386, which eventually reduced the yield components in LMM 5386.